2022
DOI: 10.1007/s10518-022-01382-3
|View full text |Cite
|
Sign up to set email alerts
|

Seismic assessment and rehabilitation of a RC structure under mainshock-aftershock seismic sequences using beam-column bonded CFRP strategy

Abstract: A mainshock is usually accompanied by a group of ground motions. In many design codes, the effects of the seismic sequences have been neglected or underestimated. Aftershocks can increase structural damage or even cause failure. The current study evaluated the seismic behavior of a rehabilitated and as-built RC structure under real scaled mainshock-aftershocks using nonlinear analysis. Verification was done in two modes. The inter-story drift ratio, maximum residual, and relative displacements were studied. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…As expected, the seismic sequences caused plastic strain as well as an increase in the drift ratio (cumulative damage), chiefly in story one [25,26,42]. Story one experienced the highest drift ratio and plastic strain and showed the greatest difference between the 3D solid model and equivalent shell-wire model results.…”
Section: Inter-story Drift Ratiosupporting
confidence: 67%
See 3 more Smart Citations
“…As expected, the seismic sequences caused plastic strain as well as an increase in the drift ratio (cumulative damage), chiefly in story one [25,26,42]. Story one experienced the highest drift ratio and plastic strain and showed the greatest difference between the 3D solid model and equivalent shell-wire model results.…”
Section: Inter-story Drift Ratiosupporting
confidence: 67%
“…The initial damage criteria of the material (concrete or steel rebars) depended on the specific strength. For ductile material (steel rebars), when the stress reached its limits, the evolution of the damage variable took an exponential form according to the fraction strain, strain rate, and displacement at failure [18,[25][26][27]. Experimental studies have shown that brittle material (concrete) under either compression or tension, the initial damage, damage evolution, or cumulative damage could be linked to the model provided by Lubliner et al [28].…”
Section: Cumulative Damage (Damage Evolution)mentioning
confidence: 99%
See 2 more Smart Citations